Amistad y enamoramiento - Aquino Benites, Sandra Noemi (2022)
The present work of professional sufficiency is entitled "Friendship and love", it was prepared as part of the area of Personal Development, Citizenship and Civics for third grade students of Secondary Education, taking into account the learning standards of the National Curriculum according to the competence corresponding to the selected cycle and performance. The basic concepts of friendship and falling in love in the adolescent stage were addressed, the purpose of the session being for students to reflect on friendship and falling in love in order to promote healthy interpersonal relationships.